2019
DOI: 10.3390/s19204586
|View full text |Cite
|
Sign up to set email alerts
|

An Augmented Reality Based Human-Robot Interaction Interface Using Kalman Filter Sensor Fusion

Abstract: In this paper, the application of Augmented Reality (AR) for the control and adjustment of robots has been developed, with the aim of making interaction and adjustment of robots easier and more accurate from a remote location. A LeapMotion sensor based controller has been investigated to track the movement of the operator hands. The data from the controller allows gestures and the position of the hand palm’s central point to be detected and tracked. A Kinect V2 camera is able to measure the corresponding motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 30 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…The problem of accurately tracking the 3D motion of a monocular camera in a known 3D environment and dynamically estimating the 3D camera location is described in [32], suggesting a fully automated landmark-based camera calibration to initialize the motion estimation and employ extended Kalman filtering techniques to track landmarks and to estimate the camera location. Kalman filter also was used in other studies such as [13,33,39,44,48] for reducing the noise in the acquired signals. Several studies have demonstrated that Kalman filter has achieved the best denoising performance when compared to other filter-based approaches [14].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of accurately tracking the 3D motion of a monocular camera in a known 3D environment and dynamically estimating the 3D camera location is described in [32], suggesting a fully automated landmark-based camera calibration to initialize the motion estimation and employ extended Kalman filtering techniques to track landmarks and to estimate the camera location. Kalman filter also was used in other studies such as [13,33,39,44,48] for reducing the noise in the acquired signals. Several studies have demonstrated that Kalman filter has achieved the best denoising performance when compared to other filter-based approaches [14].…”
Section: Related Workmentioning
confidence: 99%
“…The reliability of Kinect V2 is not lower as that of other (high cost) motion tracking systems and Kinect can be used as a reliable and valid clinical measurement tool [33,46,68]. However, such studies typically used simple poses such as standing, walking, sit down and stand up, and for more complex poses such as performing different kinds of physical exercises, the accuracy reliability still could improved using multiple Kinect sensors rather than a single sensor, which was demonstrated to fail, for example, for tracking a lying person [43].…”
Section: Related Workmentioning
confidence: 99%
“…The 3D visualization module is programmed with Unreal Engine 4, developed by Epic Games, which allows the development of games efficiently. In recent years, it has been widely used outside of gaming, especially for visualization of computer simulation [41][42][43]. Unreal Engine 4 also has a programming language called Blueprint, similar to MATLAB/Simulink.…”
Section: Field Testmentioning
confidence: 99%
“…A detailed description of digitalization processes of factories, according to the Industry 4.0 paradigm, is proposed by Belli et al [37], together with an application developed for monitoring the production and the quality control. Short and Twiddle [38] developed the digitalization of a water industry application, while Li et al [39] developed an AR application for the control and adjustment of robots during a human-robot interaction based working task. They implemented the DT of human hands by means of LeapMotion sensor and a Kinect V2 camera.…”
Section: Previous Researchesmentioning
confidence: 99%